PENGARUH KETELADANAN GURU PAK DAN POLA ASUH ORANG TUA TERHADAP KARAKTER SISWA DI SMA/SMK DI KECAMATAN BATANG TORU TAHUN PEMBELAJARAN 2025/2026 - Yuniman Gea; Hisardo Sitorus; Robinhot Sihmbing (STKIP Subang, 2026)
This study was motivated by the persistence of various character-related problems among senior high school and vocational high school students in Batang Toru District, such as lack of discipline, responsibility, honesty, social awareness, and respect toward teachers and peers. Student character is an important aspect of education that is influenced by various factors, including the exemplary behavior of Christian Religious Education (PAK) teachers and parental parenting styles. This study aimed to determine the influence of PAK teachers’ exemplary behavior on student character, the influence of parental parenting styles on student character, and the simultaneous influence of both variables on the character of senior high school and vocational high school students in Batang Toru District during the 2025/2026 Academic Year. This study employed a quantitative approach using the Ex Post Facto method. The population consisted of 200 students from SMA Negeri 1 Batang Toru, SMK Negeri 1 Batang Toru, and SMK Negeri 2 Batang Toru. The sample comprised 133 students selected using the Slovin formula with a 5% margin of error. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using descriptive statistics, simple linear regression, and multiple linear regression with the assistance of SPSS software. The results of the study showed that: (1) the exemplary behavior of PAK teachers had a positive and significant effect on student character, with a significance value of 0.011 < 0.05 and a regression coefficient of 0.500; (2) parental parenting styles did not have a significant partial effect on student character, with a significance value of 0.480 > 0.05, although the direction of influence was positive with a regression coefficient of 0.108; and (3) the exemplary behavior of PAK teachers and parental parenting styles simultaneously had a positive and significant effect on student character, with an R value of 0.810, an R Square value of 0.656, and an F value of 123.869 with a significance level of < 0.001. The findings indicate that 65.6% of the variation in student character can be explained by the exemplary behavior of PAK teachers and parental parenting styles, while the remaining 34.4% is influenced by other factors beyond the scope of this study. Based on the findings, it can be concluded that the exemplary behavior of Christian Religious Education teachers is the most dominant factor influencing student character. Therefore, efforts to improve the quality of teachers’ role-modeling behavior, as well as strengthening the synergy between schools and families, should continue to be developed to support the formation of students who are religious, honest, disciplined, responsible, and socially caring.